A method of preparing an aerogel thermal barrier coating

CN118703082BActive Publication Date: 2026-11-03CNCEC HUALU NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410908225.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2026-11-03
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

In existing technologies, the treatment cost of waste gas gel blankets is high, the recycling rate is low, and they cannot be effectively recycled. Furthermore, the treatment cost as solid waste is high.

Method used

Waste fiber aerogel felt is crushed into micro powder, mixed with additives and water, and then dispersed and stirred at high speed after adding defoamer to form an aerogel slurry. This slurry is then mixed with a resin matrix and dispersant, and hollow glass microspheres and defoamer are added to prepare an aerogel thermal insulation coating.

Benefits of technology

The prepared aerogel thermal insulation coating has excellent thermal insulation performance, low thermal conductivity, bonding strength, temperature change resistance and crack resistance, which solves the problems of low recycling rate and high treatment cost of waste aerogel felt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118703082B_ABST
    Figure CN118703082B_ABST
Patent Text Reader

Abstract

The application discloses a kind of preparation aerogel heat insulation coating method, specific steps are as follows: step 1: waste fiber aerogel felt is crushed and ground to form micro powder;Step 2: the micro powder prepared in step 1, auxiliary agent and water are mixed, and are uniformly dispersed by low-speed stirring, then defoaming agent is added, and high-speed dispersion stirring is carried out, to obtain aerogel slurry;Wherein, the auxiliary agent is one or two kinds of mixture of sodium dodecyl benzene sulfonate, sodium fatty alcohol sulfate and potassium sodium silicate;Step 3: the aerogel slurry prepared in step 2 is mixed with resin matrix, dispersing agent, and after high-speed stirring, hollow glass microspheres and defoaming agent are mixed and added, and continue high-speed stirring, to obtain the aerogel heat insulation coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating materials technology, and specifically to a method for preparing aerogel heat-insulating coatings. Background Technology

[0002] Aerogels, as a national strategic frontier new material, are shining brightly in the fields of construction, industry, environmental protection, and new energy, in line with the policy requirements of "carbon peaking" and "carbon neutrality". Silica aerogel is a novel nanoscale porous material with a porosity of over 90%. In terms of heat conduction, it can inhibit the three heat conduction pathways of convection, radiation, and conduction. Therefore, it has an extremely low thermal conductivity of 0.013 W / (m·K) at room temperature. When used as a functional filler in reflective heat-insulating coatings, it can hinder the transfer of heat in the coating through the thermal barrier effect, reduce the thermal conductivity of the reflective heat-insulating coating, and give it excellent heat insulation performance.

[0003] Aerogel composite felt is made by combining nano-aerogel with substrates such as glass fiber and ceramic fiber. This perfectly combines the excellent properties of aerogel with a flexible substrate, maximizing the retention of the lightweight and heat-insulating characteristics of aerogel while imparting flexibility and toughness. The product is suitable for temperatures ranging from -200℃ to 1000℃. However, the manufacturing process of aerogel composite felt generates a large amount of aerogel felt scraps and waste from quality and performance testing. Currently, the recycling rate of this waste is almost zero, and its disposal as solid waste is costly. Summary of the Invention

[0004] In view of the above-mentioned shortcomings of the existing technology, the purpose of the present invention is to provide a method for preparing aerogel thermal insulation coating, so as to solve the problems that the existing technology cannot recycle waste aerogel felt and has high cost for solid waste treatment.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0006] A method for preparing aerogel thermal insulation coating, comprising the following specific steps:

[0007] Step 1: Crush and grind the fiber aerogel felt into micro powder with a particle size of 10-50 μm; the fiber aerogel felt is one of the following: waste glass fiber aerogel felt, waste glass fiber / PET blended fiber aerogel felt, waste carbon fiber aerogel felt, and waste ceramic fiber aerogel felt.

[0008] Step 2: Mix the micro powder, additives, and water prepared in Step 1, and stir at low speed to disperse them evenly. Then add the defoamer and disperse and stir at high speed to obtain an aerogel slurry. The additives are sodium dodecylbenzene sulfonate, sodium fatty alcohol sulfate, or a mixture of two of them and sodium potassium silicate. The mass ratio of micro powder, additives, and water is 1:(0.1-0.5):(4.0-5.0).

[0009] Step 3: Mix the aerogel slurry prepared in Step 2 with the resin matrix and dispersant, and stir at high speed. Then add hollow glass microspheres and defoamer, mix, and continue stirring at high speed to obtain the aerogel heat insulation coating. The mass ratio of aerogel slurry, resin matrix, and dispersant is 1:(2.5~3.5):(0.1~0.5). The amount of hollow glass microspheres added is 0.5~1 part by weight, and the amount of defoamer added is 0.1~0.5 parts. The resin matrix is ​​styrene-acrylic emulsion.

[0010] Preferably, in step 2, the low-speed stirring speed is 600-800 rpm / min and the stirring time is 15-20 min; the high-speed dispersion stirring speed is 1500-20000 rpm / min and the stirring time is 15-20 min.

[0011] Preferably, in step 3, the high-speed stirring speed is 1500-2000 rpm / min, and the stirring time is 15-30 min.

[0012] Preferably, the dispersant is SN5040.

[0013] Preferably, the SiO2 aerogel content in the glass fiber aerogel felt is 50-60% by mass percentage.

[0014] Preferably, in the glass fiber / PET blended fiber aerogel felt, the SiO2 aerogel content accounts for 60-70% by mass percentage; and the blended fiber is composed of 45%-55% alkali-free glass fiber and 45%-55% PET fiber by mass percentage.

[0015] Preferably, the ceramic fiber aerogel felt is composed of ceramic fiber needle-punched felt and SiO2 aerogel in situ composite, with the SiO2 aerogel content accounting for 40-50% by mass percentage.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. This invention addresses the problems of high treatment costs and low recycling rates of existing fiber aerogel felt solid waste. It involves crushing and pulverizing waste aerogel felt to obtain aerogel micropowder, which is then used as a functional filler to prepare aerogel thermal insulation coatings. The aerogel thermal insulation coating prepared by this invention not only possesses excellent thermal insulation performance and extremely low thermal conductivity, but also exhibits excellent bonding strength, resistance to temperature changes, impact resistance, and crack resistance.

[0018] 2. This invention redesigns the preparation process of aerogel thermal insulation coatings. After the aerogel thermal insulation coating is dried and formed into a film, the silica network skeleton formed together with the reinforcing fibers (glass fibers, blended fibers and ceramic fibers) constitutes a stable three-dimensional network structure, which plays a good skeletal support role for the coating. Different types of additives are suitable for different reinforcing fibers, which is beneficial to the dispersion and connection of various fibers in the coating system.

[0019] 3. The aerogel thermal insulation coating prepared by adding fiber aerogel micro powder in this invention has low density, low thermal conductivity, no cracking, and high bonding strength. At the same time, due to the high temperature resistance (glass fiber and ceramic fiber) or low temperature resistance (blended fiber) properties of the fiber components, the prepared aerogel thermal insulation coating has excellent temperature deformation resistance and a wide applicable temperature range.

[0020] 4. Compared with existing aerogel thermal insulation coatings, this invention solves the problem of easy cracking of existing aerogel thermal insulation coatings, enhances the toughness and stability of aerogel coatings, improves their adhesion and crack resistance, and has the advantages of taking into account low thermal conductivity, temperature change resistance and impact resistance. Moreover, all performance indicators are excellent and it is suitable for thermal insulation conditions from -50℃ to 400℃. Attached Figure Description

[0021] Figure 1 This is a flowchart of the method described in this invention.

[0022] Figure 2 Images of aerogel coating samples prepared in Examples 1-3 and Comparative Example 1. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the present invention are within the scope of protection of the present invention.

[0024] Unless otherwise specified in the specific circumstances, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within that range, but are not limited to the specific values ​​listed when the range is defined.

[0025] I. A method for preparing aerogel thermal insulation coating

[0026] The process flow of the method described in this invention is as follows: Figure 1 As shown, the specific steps are as follows:

[0027] Step 1: Crush and grind the fiber aerogel felt into micro powder with a particle size of 10-50 μm; the fiber aerogel felt is one of the following: waste glass fiber aerogel felt, waste glass fiber / PET blended fiber aerogel felt, waste carbon fiber aerogel felt, and waste ceramic fiber aerogel felt.

[0028] Step 2: Mix the micro powder, additives, and water prepared in Step 1, and stir at low speed to disperse them evenly. Then add the defoamer and disperse and stir at high speed to obtain an aerogel slurry. The additives are sodium dodecylbenzene sulfonate, sodium fatty alcohol sulfate, or a mixture of two of them and sodium potassium silicate. The mass ratio of micro powder, additives, and water is 1:(0.1-0.5):(4.0-5.0).

[0029] Step 3: Mix the aerogel slurry prepared in Step 2 with the resin matrix and dispersant, and stir at high speed. Then add hollow glass microspheres and defoamer, mix, and continue stirring at high speed to obtain the aerogel heat insulation coating. The mass ratio of aerogel slurry, resin matrix, and dispersant is 1:(2.5~3.5):(0.1~0.5). The amount of hollow glass microspheres added is 0.5~1 part by weight, and the amount of defoamer added is 0.1~0.5 parts. The resin matrix is ​​styrene-acrylic emulsion.

[0030] In actual production, this invention discovered that a large amount of aerogel felt scraps and waste materials from quality and performance testing are generated during the manufacturing of aerogel composite felt. Currently, the recycling rate of these waste materials is almost zero, and they can only be treated as solid waste. However, the cost of treating such solid waste is very high. Therefore, this invention aims to explore new uses for these aerogel felt waste materials. This invention envisions making aerogel insulation coatings from these aerogel felts. However, existing aerogel insulation coatings made from aerogel felts suffer from drawbacks such as easy cracking, poor adhesion, and an inability to simultaneously achieve both insulation and mechanical properties. This invention, while envisioning the production of aerogel insulation coatings from these waste aerogel felts, also considers addressing the aforementioned drawbacks. Based on one of the following raw materials: waste glass fiber aerogel felt, waste glass fiber / PET blended fiber aerogel felt, waste carbon fiber aerogel felt, or waste ceramic fiber aerogel felt, additives are added. The additives are based on sodium potassium silicate and used in combination with one or two of sodium dodecylbenzenesulfonate and sodium fatty alcohol sulfate. Of these three additives, sodium potassium silicate is the foundation, serving as a glass toughening agent that helps improve the dispersibility, toughness, and heat resistance of glass and ceramic fibers in coatings. It also acts as a waterproofing agent and adhesive, enhancing the water resistance and bonding strength of the coating. Sodium dodecylbenzene sulfonate and sodium fatty alcohol sulfate can be used in combination with sodium potassium silicate, or all three can be added simultaneously. Sodium dodecylbenzene sulfonate and sodium fatty alcohol sulfate, as high-performance anionic surfactants, possess excellent emulsifying and dispersing abilities, which can improve the bonding strength between the emulsion and waste aerogel felt. However, these three additives cannot be used alone; using them alone will not significantly improve the coating's performance and will be insufficient to address the problems of cracking and poor adhesion.

[0031] The styrene-acrylic emulsion in this embodiment of the invention is obtained by emulsion copolymerization of styrene and acrylate monomers. Compared with other emulsions, the styrene-acrylic emulsion, as a film-forming substance, has good adhesion and can be applied to various substrate surfaces, such as steel, plastics, and concrete, without cracking or shrinkage. Other emulsions, however, struggle to address these issues. The amounts of hollow glass microspheres and defoamer are calculated based on the total mass of the aerogel slurry, resin matrix, and dispersant. Specifically, the hollow glass microspheres account for 0.5–1% of the total mass of the aerogel slurry, resin matrix, and dispersant, and the defoamer accounts for 0.1–0.5% of the total mass. The weight percentages in the examples are also calculated according to this ratio. Conventional defoamers from the prior art can be used as the defoamer.

[0032] In some embodiments, the fiber aerogel felt is pulverized and ground into micro powder, and the particle size of the micro powder is controlled between 10 and 50 μm.

[0033] In some embodiments, in step 2, the low-speed stirring speed is 600-800 rpm / min and the stirring time is 15-20 min; the high-speed dispersion stirring speed is 1500-2000 rpm / min and the stirring time is 15-20 min.

[0034] In some embodiments, in step 3, the high-speed stirring speed is 1500-2000 rpm / min, and the stirring time is 15-30 min.

[0035] In some embodiments, the dispersant is SN5040.

[0036] In some embodiments, the glass fiber aerogel felt has a thermal conductivity of ≤0.020W / (m·K) at 25℃, a volume water absorption rate of ≤1%, a combustion performance of A(A1) grade as specified in GB 8624, a maximum service temperature of 650℃, and a SiO2 aerogel content of 50-60% by mass percentage.

[0037] In some embodiments, the glass fiber / PET blended fiber aerogel felt has a thermal conductivity of ≤0.016 W / (m·K) at 25℃, a volume water absorption rate of ≤1%, a combustion performance not lower than the B1(C) level specified in GB 8624, and a minimum service temperature of 200℃. It is composed of glass fiber / PET blended fiber needle-punched felt and SiO2 aerogel in situ composite. Calculated by mass percentage, the SiO2 aerogel content in the glass fiber / PET blended fiber aerogel felt accounts for 60-70%; calculated by mass percentage, the blended fiber consists of 45%-55% alkali-free glass fiber and 45%-55% PET fiber.

[0038] In some embodiments, the ceramic fiber aerogel felt is composed of ceramic fiber needle-punched felt and SiO2 aerogel in situ composite, with the SiO2 aerogel content accounting for 40-50% by mass percentage. The ceramic fiber aerogel felt has a thermal conductivity of ≤0.021W / (m·K) at 25℃, a combustion performance of Class A (A1) as specified in GB 8624, and a maximum service temperature of 1000℃.

[0039] II. Examples and Comparative Examples

[0040] Example 1

[0041] Step 1: Preparation of glass fiber aerogel powder: Glass fiber aerogel mat is processed by a pulverizer and mill to obtain glass fiber aerogel powder with a particle size of 10-50 μm.

[0042] Step 2: Preparation of glass fiber aerogel slurry: The glass fiber aerogel powder, potassium sodium silicate, sodium dodecylbenzenesulfonate, and deionized water prepared in Step 1 are mixed in a mass ratio of 1:0.15:0.1:4.5. The mixture is dispersed and stirred at a low speed of 800 rpm / min for 30 min. During the process, 0.35 parts of defoamer are added, and the mixture is dispersed and stirred again at a high speed of 1700 rpm / min for 20 min to obtain the glass fiber aerogel slurry. Here, the amount of 0.35 parts of defoamer refers to the amount of defoamer added accounting for 0.35% of the total mass of the glass fiber aerogel powder, potassium sodium silicate, sodium dodecylbenzenesulfonate, and deionized water. Examples 2 and 3 follow the same principle.

[0043] Step 3: Preparation of fiber aerogel thermal insulation coating: The glass fiber aerogel slurry, styrene-acrylic emulsion, and dispersant SN5040 prepared in Step 2 are mixed at a mass ratio of 1:3.0:0.35 and dispersed at 1800 rpm / min for 30 min. Then, 0.75 parts of hollow glass microspheres and 0.35 parts of defoamer are added and mixed. The mixture is then dispersed at 2000 rpm / min for 20 min to obtain the final glass fiber aerogel thermal insulation coating. Here, the amount of hollow glass microspheres and defoamer added is calculated based on the total mass of the glass fiber aerogel slurry, styrene-acrylic emulsion, and dispersant. The amount of hollow glass microspheres added accounts for 0.75% of the total mass of the three components, and the amount of defoamer added accounts for 0.35% of the total mass of the three components. Examples 2 and 3 follow the same principle.

[0044] The dry density of the glass fiber aerogel thermal insulation coating sample prepared above is 203 kg / m³. 3 According to GB / T 10294-2008, the thermal conductivity at 25℃ is 0.03772W / (m·K).

[0045] Example 2

[0046] Step 1: Preparation of blended fiber aerogel powder: The blended fiber aerogel felt is processed by a pulverizer to obtain blended fiber aerogel powder with a particle size of 10-50 μm.

[0047] Step 2: Preparation of blended fiber aerogel slurry: The blended fiber aerogel powder, potassium sodium silicate, sodium fatty alcohol sulfate, and deionized water prepared in Step 1 are mixed at a mass ratio of 1:0.1:0.15:4.5 and dispersed and stirred at a low speed of 800 rpm / min for 30 min. During the process, 0.35 parts of defoamer are added and dispersed and stirred again at a high speed of 1700 rpm / min for 20 min to obtain the blended fiber aerogel slurry.

[0048] Step 3: Preparation of fiber aerogel thermal insulation coating: The blended fiber aerogel slurry, styrene-acrylic emulsion, and dispersant SN5040 prepared in Step 2 are mixed at a mass ratio of 1:3.5:0.4 and dispersed at 1800 rpm / min for 30 min. Then, 0.65 parts of hollow glass microspheres and 0.35 parts of defoamer are added and mixed. The mixture is then dispersed at 2000 rpm / min for 20 min to obtain the blended fiber aerogel thermal insulation coating.

[0049] The dry density of the blended fiber aerogel thermal insulation coating sample prepared above is 191 kg / m³. 3 According to GB / T 10294-2008, the thermal conductivity at 25℃ is 0.03538 W / (m·K).

[0050] Example 3

[0051] Step 1: Preparation of ceramic fiber aerogel powder: Ceramic fiber aerogel felt is processed by a pulverizer to obtain ceramic fiber aerogel powder with a particle size of 10-50 μm;

[0052] Step 2: Preparation of ceramic fiber aerogel slurry: The ceramic fiber aerogel powder, potassium sodium silicate, sodium dodecylbenzene sulfonate, and deionized water prepared in Step 1 are mixed at a mass ratio of 1:0.15:0.1:4.5 and dispersed and stirred at a low speed of 800 rpm / min for 30 min. During the process, 0.35 parts of defoamer are added and dispersed and stirred again at a high speed of 1700 rpm / min for 20 min to obtain ceramic fiber aerogel slurry.

[0053] Step 3: Preparation of fiber aerogel thermal insulation coating: The ceramic fiber aerogel slurry, styrene-acrylic emulsion, and dispersant SN5040 prepared in Step 2 are mixed at a mass ratio of 1:3.5:0.35 and dispersed at 1800 rpm / min for 30 min. Then, 0.8 parts of hollow glass microspheres and 0.35 parts of defoamer are added and mixed. The mixture is then dispersed at 2000 rpm / min for 20 min to obtain the final ceramic fiber aerogel thermal insulation coating.

[0054] The dry density of the ceramic fiber aerogel thermal insulation coating sample prepared above is 212 kg / m³. 3 According to GB / T 10294-2008, the thermal conductivity at 25℃ is 0.04217 W / (m·K).

[0055] Comparative Example 1

[0056] The method was adjusted based on Example 1, the difference being that: no aerogel powder containing fiber components was added in Comparative Example 1, and only sodium dodecylbenzenesulfonate was added as a dispersant, without the addition of sodium potassium silicate. Other raw materials, dosages, and preparation methods were the same as in Example 1.

[0057] The dry density of the aerogel thermal insulation coating sample prepared above is 177 kg / m³. 3 According to GB / T 10294-2008, the thermal conductivity at 25℃ is 0.03853 W / (m·K).

[0058] Comparative Example 2

[0059] The method of making adjustments based on Example 1 is as follows: Comparative Example 2 uses a nonionic surfactant JCF (fatty alcohol polyvinyl ether), while other raw materials, dosages, and preparation methods are the same as in Example 1.

[0060] Compared with sodium potassium silicate and sodium dodecylbenzene sulfonate in Example 1, the JCF used in this comparative example had poor dispersion of the prepared fiber aerogel slurry, and the prepared aerogel coating exhibited demulsification, which affected the final film formation and prevented the obtaining of a complete aerogel coating surface-dried sample.

[0061] The performance parameters of the aerogel thermal insulation coatings prepared in Examples 1-4 of this invention are shown in Table 1. The test standard for thermal conductivity is GB / T 10297-2015, and the test standard for adhesive strength is JG / T 157-2009.

[0062] Table 1 Performance parameters of aerogel thermal insulation coating

[0063]

[0064]

[0065] The aerogel coating sample of Comparative Example 1 showed slight surface cracking, while the aerogel coating samples in Examples 1-3 did not show surface cracking (see attached). Figure 2 This indicates that the addition of fiber components enables the silica mesh skeleton and reinforcing fibers to form a stable three-dimensional network structure, providing good skeletal support for the coating and alleviating the cracking problem of the aerogel coating. Table 1 shows that the thermal conductivity of samples from Examples 1-3 is all <0.045 W / (m·K), and the bond strength is higher than that of Comparative Example 1. This indicates that the addition of fiber components and suitable additives can not only enhance the toughness and stability of the aerogel coating, improve its adhesion and crack resistance, but also better maintain the thermal insulation performance of the aerogel coating.

[0066] Table 1 shows that, due to the high-temperature resistance of glass fiber and ceramic fiber, the aerogel thermal insulation coatings prepared in Examples 1 and 3 of this invention exhibit excellent thermal insulation performance. After 10 minutes of high-temperature treatment at 400℃, the cold surface temperature of the prepared coatings is below 120℃. This indicates that the invention not only allows for the recycling of solid waste aerogel felt, but also enhances the high-temperature resistance of the aerogel coating through its fiber components.

[0067] The dispersing agents used in Comparative Example 2 and the examples are of different types. In the examples, sodium potassium silicate is used as a glass toughening agent, while sodium dodecylbenzenesulfonate and sodium fatty alcohol sulfate are anionic surfactants. In Comparative Example 2, JCF (fatty alcohol polyvinyl ether) is a nonionic surfactant. Anionic surfactants can ionize in aqueous coating systems to generate anions, i.e., hydrophilic groups in the surfactant, which facilitates the dispersion of fiber aerogel powder in emulsions and water. The aerogel coating finally prepared in Comparative Example 2 was difficult to form a film. This indicates that not just any surfactant can play the role of the additives described in this invention. It also illustrates that in existing aerogel coating systems, the selection of dispersing agents is crucial for the dispersion and bonding of fiber components. Appropriate additives must be selected to ensure smooth film formation while maintaining good adhesion and crack resistance.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit the technical solutions. Those skilled in the art should understand that any modifications or equivalent substitutions to the technical solutions of the present invention without departing from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing aerogel thermal insulation coating, characterized in that, The specific steps are as follows: Step 1: Crush and grind the fiber aerogel felt into micro powder with a particle size of 10~50μm; the fiber aerogel felt is one of the following: waste glass fiber aerogel felt, waste glass fiber / PET blended fiber aerogel felt, waste carbon fiber aerogel felt, and waste ceramic fiber aerogel felt; the fiber aerogel felt contains fiber components; calculated by mass percentage, the SiO2 aerogel content in glass fiber aerogel felt is 50~60%, the SiO2 aerogel content in glass fiber / PET blended fiber aerogel felt is 60~70%, and the SiO2 aerogel content in ceramic fiber aerogel felt is 40~50%; Step 2: Mix the micro powder, additives, and water obtained in Step 1, and stir at low speed to disperse them evenly. Then, add the defoamer and disperse and stir at high speed to obtain an aerogel slurry. The additives are sodium dodecylbenzene sulfonate, sodium fatty alcohol sulfate, or a mixture of two of them and sodium potassium silicate. The mass ratio of micro powder, additives, and water is 1:(0.1~0.5):(4.0~5.0). Step 3: Mix the aerogel slurry prepared in Step 2 with the resin matrix and dispersant, and stir at high speed. Then add hollow glass microspheres and defoamer, mix, and continue stirring at high speed to obtain the aerogel heat insulation coating. The mass ratio of aerogel slurry, resin matrix, and dispersant is 1:(2.5~3.5):(0.1~0.5). The amount of hollow glass microspheres and defoamer added is calculated based on the total mass of the aerogel slurry, resin matrix, and dispersant. The amount of hollow glass microspheres added accounts for 0.5~1% of the total mass of the three components, and the amount of defoamer added accounts for 0.1~0.5% of the total mass of the three components. The resin matrix is ​​a styrene-acrylic emulsion.

2. The method according to claim 1, characterized in that, In step 2, the low-speed stirring speed is 600~800 rpm and the stirring time is 15~20 min; the high-speed dispersion stirring speed is 1500~2000 rpm and the stirring time is 15~20 min.

3. The method according to claim 1, characterized in that, In step 3, the high-speed stirring speed is 1500~2000 rpm, and the stirring time is 15~30 min.

4. The method according to claim 1, characterized in that, The dispersant is SN5040.

5. The method according to claim 1, characterized in that, In the glass fiber / PET blended fiber aerogel felt, the blended fiber is composed of 45%~55% alkali-free glass fiber and 45%~55% PET fiber, calculated by mass percentage.

6. The method according to claim 1, characterized in that, The ceramic fiber aerogel felt is composed of ceramic fiber needle-punched felt and SiO2 aerogel in situ composite.

Citation Information

Patent Citations

  • Light super-strong aerogel heat insulation coating and preparation method thereof

    CN113248950A

  • Fiber felt with heat insulation performance and preparation method thereof

    CN114808275A

  • Water-based thermal insulation coating prepared from hydrophobic silicon dioxide aerogel and preparation method of water-based thermal insulation coating

    CN117126571A